Features of state administration in the field of social defence in countries of SND - Калюжний, Ростислав Андрійович; Шевченко, Анатолій Євгенович; Гончаров, Андрій Вікторович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article the features of realization of social defence of population in the countries of SND are analysed and possibilities of the use of positive experience are certain, and also directions of further perfection of social defence of population are offered in Ukraine.